Effective redressal of public grievances - Srinivas, V. (New Delhi Department of administrative reforms and public grievances, 2023)
Prime Minister Modi has said "Effective Redressal of Public Grievances" is one of the most important aspects of Indian democracy, accorded highest priority to the subject with focus on citizen engagement.
Keywords: V. Srinivas, IAS